PERKAWINAN BEDA AGAMA SECARA ALKITABIAH DALAM MASYARAKAT PLURALISME - Jessica Silfanus (Sekolah Tinggi Teologi Bethel The Way Jakarta, 2022)
Interfaith marriages in a pluralistic society often occur due to the diversity of religious adherents in Indonesia. The problem is that when the commitment does not go well, then the relationship will become complicated. The result is the disruption of the harmony of married life because there is no role of religion in the purpose of the marriage bond. The purpose of writing this article is to look at the biblical perspective on interfaith marriage in a pluralistic society. The true foundation of marriage in Christianity or in other religions. The method used for this research is a qualitative method of library studies. The causes of interfaith marriages are social life, minimal religious education, parental background, and the current of globalization also encourage new social constructions. Interfaith marriages in the Old and New Testaments are not permitted by God, because marriage is God's initiative and must be centered on Jesus Christ. Marriage must Return to carry out God's eternal plan so that marriage can achieve its original purpose, namely humans must Return to God and His Word to understand it. This is the reason God wants marriage to be a marriage of faith. Marriage is the foundation because it is on this relationship that God begins to build society. Healthy marriages must be built and run according to Christ and these relationships are based on Christ as the head of the family and church.